Pengaruh Komitmen Organisasi dan Kualitas Kerja terhadap Kepuasan Kerja Serta Dampaknya pada Kinerja Karyawan PT. Indofood CBP Sukses Makmur Cabang Jambi - Harahap, Sihar Martuah; Suryani, Arna; Yamali, Fakhrul Rozi (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research is to describe organizational commitment, work quality, job satisfaction and employee performance at PT. Indofood CBS Sukses Makmur Jambi Branch and to analyze the influence of organizational commitment and work quality partially and simultaneously directly and indirectly on job satisfaction and employee performance, as well as to analyze job satisfaction on employee performance. From the path analysis tests carried out, it was found that organizational commitment and work quality had an influence on job satisfaction by 77.4% while the rest was influenced by other variants. Organizational commitment and work quality have an influence of 77.2% on employee performance at PT. Indofood CBS Successfully Prosperous Jambi Branch. This research concludes that organizational commitment, work quality, job satisfaction and employee performance are quite satisfied and high. Apart from that, organizational commitment and work quality partially and simultaneously have a positive and significant influence on job satisfaction and employee performance at PT. Indofood CBS Successfully Prosperous Jambi Branch. Likewise, job satisfaction has a positive and significant influence on employee performance.